HUBUNGAN REAKSI LIMFOSIT DENGAN DERAJAT KEGANASAN KANKER SERVIKS DI RSUD ULIN BANJARMASIN PERIODE JANUARI-DESEMBER 2013 - Hanafi, Ahmad Marzuki Rifki; Oktaviyanti, Ika Kustiyah; Istiana, Istiana (Jurnal Berkala Kedokteran, 2015)
Cervix cancer is a malignancy in women at most 3rd in the world, which occurs in the cervix uteri. Etiologic factor of cervix cancer is infection with human papilloma virus (HPV). Lymphocyte very important role in eradicating cancer cells. However, cervix cancer mortality rates remain high, especially in poor differentiated grade. This may be related to the level of mixed lymphocyte reaction and depending on the status of the tumor grade. This study aimed to determine the correlation between lymphocyte reaction with tumor grade in patients with cervix cancer in RSUD Ulin Banjarmasin period from January to December 2013. The study design was observational analytic study with cross-sectional approach. The data were taken in the form of primary data in the form of checks degrees lymphocytes with a microscope. The population is all women who underwent histopathological examination in RSUD Ulin period from January to December 2013. The sample was taken by purposive sampling as many as 56 people who had met the inclusion criteria. The results showed that the incidence of cervix cancer well-differentiated at most that 25 cases (44%) and lymphocyte reaction that many are mild lymphocyte reaction as much as 33 cases (59%). Somersd test analysis in the study obtained value (aprox sig. = 0.761). These results indicate that there is no significant correlation between lymphocyte reaction with tumor grade cervix cancer in RSUD Ulin period from January to December 2013.Â Keywords: cervix cancer, tumor grade, lymphocyte reaction